2016
DOI: 10.2196/jmir.4335
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Physical Activity Intervention to Improve Quality of Life of Inactive Older Adults: A Randomized Controlled Trial

Abstract: BackgroundIncreasing physical activity is a viable strategy for improving both the health and quality of life of older adults.ObjectiveThe aim of this study was to assess if an Internet-based intervention aimed to increase physical activity was effective in improving quality of life of inactive older adults. In addition, we analyzed the effect of the intervention on quality of life among those participants who successfully reached their individually targeted increase in daily physical activity as indicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 23 publications
1
83
1
1
Order By: Relevance
“…9 Maintaining this gap results in the accumulated health benefit in terms of QALYs over time. 10 Although some studies have found that PA can increase QOL among sedentary older adults, 23,24 these studies typically use shorter assessment follow-up periods, and use QOL measures that have multiple subscales (e.g., Short Form-36) that could increase chances of finding improvement because of multiple comparisons. 25 LIFE assessed QOL every 6 months for up 30 months, and used the single total summary QWB-SA score.…”
Section: Discussionmentioning
confidence: 99%
“…9 Maintaining this gap results in the accumulated health benefit in terms of QALYs over time. 10 Although some studies have found that PA can increase QOL among sedentary older adults, 23,24 these studies typically use shorter assessment follow-up periods, and use QOL measures that have multiple subscales (e.g., Short Form-36) that could increase chances of finding improvement because of multiple comparisons. 25 LIFE assessed QOL every 6 months for up 30 months, and used the single total summary QWB-SA score.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback and rewards are other behavior change techniques closely tied to goal setting that can be effective for increasing activity (28, 34, 4244). Feedback can be as basic as providing access to step counts, or more tailored messages designed to motivate activity.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…This entails receiving directions or instructions from a peer or a professional. Coaching is often used in interventions and fitness technology to motivate increases in physical activity (44, 5557). One intervention utilized professional coaching via weekly information sessions that encouraged healthy behaviors and a weekly 30-min group walking session (58).…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…Among European studies, three were conducted in the Netherlands (47,48,50), two in the UK (46,52), and one in three countries (Greece, Spain and Sweden) (41). Furthermore, three studies presented different parts of their results in distinct publications: (i) Wijsman et al (50,54,55); (ii) van het Reve et al (49,56,57); and (iii) Peels et al (47,(58)(59)(60)(61)(62). When appraising the quality of the retained studies, we first noted that great variation existed with regard to sample size with a minimum of 14 and a maximum of 1729 participants.…”
Section: Resultsmentioning
confidence: 99%